Geomechanical and Technical Aspects of Torpedo Blasting under Seismic and Rockburst Hazard Conditions in Legnica–Glogow Copper District Mines - Zbigniew Burtan; Jerzy Cieślik; Dariusz Chlebowski; Paweł Piasecki; Krzysztof Gzik (Energies, 2024)
The dominant hazard in the Polish copper ore mining industry (LGCD mines—Legnica–Glogow Copper District) is the occurrence of mining tremors and rockbursts. One of the effective active methods of preventing this threat is torpedo blasting, which results in disturbing the structure of roof rocks. A change in the integrity of a roof, especially in the tremor-generating layer or in the contact between stiff rock layers, reduces the possibility of an elastic energy concentration and may also be a kind of stress concentrator, provoking the destruction of rocks. This article presents original solutions for determining the areas of rock mass within a mining area where it is advisable to conduct torpedo blasting, and the experience of blasting in the Rudna copper mine in the LGCD is described. The first part of this article presents the results and experiences of using torpedo blasting prevention in the LGCD mine conditions in the Rudna mine. Assuming that due to the stress of the rocks, torpedo blasting brings the greatest benefits in the areas of elastic energy concentration, the second part of this article presents the results of numerical modeling, on the basis of which the zones of elastic energy concentration in the form of total, shear and volume deformation were determined in the vicinity of mining activities for typical geological and mining conditions in the LGCD. The importance of methods for the verification of the proposed solutions based on the analysis of seismic activity and geophysical mechanisms of events’ foci and seismo-acoustic emissions was also emphasized. The numerical simulations performed and conclusions from in situ observations allowed the formulation of general principles for the selection of torpedo blasting parameters.